2009
DOI: 10.4049/jimmunol.0902707
|View full text |Cite
|
Sign up to set email alerts
|

Langerin+CD8α+ Dendritic Cells Are Critical for Cross-Priming and IL-12 Production in Response to Systemic Antigens

Abstract: Distinct dendritic cell (DC) subsets differ with respect to pathways of Ag uptake and intracellular routing to MHC class I or MHC class II molecules. Murine studies suggest a specialized role for CD8α+ DC in cross-presentation, where exogenous Ags are presented on MHC class I molecules to CD8+ T cells, while CD8α− DC are more likely to present extracellular Ags on MHC class II molecules to CD4+ T cells. As a proportion of CD8α+ DC have been shown to express langerin (CD207), we investigated the role of langeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(161 citation statements)
references
References 63 publications
11
150
0
Order By: Relevance
“…DCs from the spleen are heterogeneous, and recent studies suggested that DC subsets could differ in their ability to stimulate iNKT cells (26,45,46). For example, we have previously reported that among the CD8a 2 DC subset, CD4 2 DCs were more efficient at activating iNKT cells, relative to CD4 + DCs (45).…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 99%
See 1 more Smart Citation
“…DCs from the spleen are heterogeneous, and recent studies suggested that DC subsets could differ in their ability to stimulate iNKT cells (26,45,46). For example, we have previously reported that among the CD8a 2 DC subset, CD4 2 DCs were more efficient at activating iNKT cells, relative to CD4 + DCs (45).…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 99%
“…In the mouse system, DCs in the spleen, an important site of immune responses to blood-borne Ag, are mainly composed of CD8a + DCs, a subset specialized in Ag crosspresentation, and of CD8a 2 DCs, a subset more efficient at presenting Ag on MHC class II (24). Recent findings indicated that CD8a + DCs are particularly potent to activate iNKT cells (25) and to trigger iNKT cell-based innate immune responses (26,27). These data, and the fact that CD8a + DCs excel in Ag crosspresentation, prompted us to actively deliver a-GalCer and Ag to CD8a + DCs in vivo.…”
mentioning
confidence: 99%
“…lang-EGFP hosts were used to identify langerin The interaction between DCs and NKT cells involves CD40-CD40 ligand interaction that contributes to significant production of IL-12, primarily from langerin 1 CD8a 1 DCs. 44 Serum IL-12 was analyzed 5 hours after vaccine administration in the presence or absence of established leukemia, and similar levels were observed ( Figure 2L). Together, these results indicate that the inefficacy of the vaccine was not attributed to a failure to activate NKT cells or DCs.…”
Section: Resultsmentioning
confidence: 91%
“…[44][45][46] To establish whether langerin 1 DCs were involved in the protection afforded by the leukemia/a-GalCer vaccine, lang-EGFPDTR hosts were depleted of langerin-expressing cells by DT treatment before vaccination, as previously described. 44 This led to complete abrogation of the protective effect of leukemia/a-GalCer ( Figure 1F), indicating that langerin 1 DCs are essential for vaccine efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation